Effect of high roughness on a long aging time of superhydrophilic TiO 2 nanoparticle thin films - Thongsuwan W. (2014)
TiO2 nanoparticle thin films with a high roughness were successfully deposited on quartz substrates by a sparking process. To obtain a uniform film thickness, the substrate was moved raster-like across an area of 1 × 1 cm2 by the x-y scanning stage. Effects of annealing temperatures on surface morphology, chemical structure, photocatalytic and wetting properties were examined by scanning and transmission electron microscopy, atomic force microscopy, Raman spectroscopy, UV-vis spectroscopy and contact angle measurement, respectively. The sample annealed at the optimum temperature of 500 °C shows the highest RMS roughness, photocatalytic activity and also the lowest water contact angle. An optimum anatase/rutile ratio and maximum RMS roughness were believed to be the reason for the above results. In contrast with most previous reports, the films prepared by this process remain highly superhydrophilic after 5 weeks without UV exposure. © 2011 Elsevier B.V. All rights reserved.